Sex differences in primary muscle afferent sensitization following ischemia and reperfusion injury - Jessica L. Ross; Luis F. Queme; Jordan E. Lamb; Kathryn J. Green; Michael P. Jankowski (Biology of Sex Differences, 2018)
Abstract Background Chronic pain conditions are more prevalent in women, but most preclinical studies into mechanisms of pain generation are performed using male animals. Furthermore, whereas group III and IV nociceptive muscle afferents provoke central sensitization more effectively than their cutaneous counterparts, less is known about this critical population of muscle nociceptors. Here, we compare the physiology of individual muscle afferents in uninjured males and females. We then characterize the molecular, physiological, and behavioral effects of transient ischemia and reperfusion injury (I/R), a model we have extensively studied in males and in females. Methods Response properties and phenotypes to mechanical, thermal, and chemical stimulation were compared using an ex vivo muscle/nerve/dorsal root ganglia (DRG)/spinal cord recording preparation. Analyses of injury-related changes were also performed by assaying evoked and spontaneous pain-related behaviors, as well as mRNA expression of the affected muscle and DRGs. The appropriate analyses of variance and post hoc tests (with false discovery rate corrections when needed) were performed for each measure. Results Females have more mechanically sensitive muscle afferents and show greater mechanical and thermal responsiveness than what is found in males. With I/R, both sexes show fewer cells responsive to an innocuous metabolite solution (ATP, lactic acid, and protons), and lower mechanical thresholds in individual afferents; however, females also possess altered thermal responsiveness, which may be related to sex-dependent changes in gene expression within the affected DRGs. Regardless, both sexes show similar increases in I/R-induced pain-like behaviors. Conclusions Here, we illustrate a unique phenomenon wherein discrete, sex-dependent mechanisms of primary muscle afferent sensitization after ischemic injury to the periphery may underlie similar behavioral changes between the sexes. Furthermore, although the group III and IV muscle afferents are fully developed functionally, the differential mechanisms of sensitization manifest prior to sexual maturity. Hence, this study illustrates the pressing need for further exploration of sex differences in afferent function throughout the lifespan for use in developing appropriately targeted pain therapies.